Kualitas kimia susu Kambing Sapera (Saanen Peranakan Etawah) di Wayang Dairy Farm, Kabupaten Bandung - Ajat Sudrajat; Yuli Perwita Sari; Raden Febrianto Christi; Asep Rahmat Khaerudin (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
Research on the chemical quality of Sapera goat milk at Wayang Dairy Farm Bandung Regency has been carried out. This study aimed to determine and examine the chemical quality of fresh milk in the dairy company Wayang Dairy Farm. This research was conducted in May-June 2023 at Wayang Dairy Farm, Pangalengan District, Bandung, Laboratory of Nutrition and Animal Product Technology, Faculty of Agroindustry, Universitas Mercu Buana Yogyakarta and Food Technology and Agricultural Products test laboratory, Faculty of Agricultural Technology, Universitas Gadjah Mada. The research method used a survey method and tested the chemical quality of fresh milk from the morning milking of 10 Sapera goats. The observed parameters of the chemical quality of fresh milk are protein content, fat and specific gravity of milk. The collected test result data is then tabulated and averaged using MS. Office Excel and analyzed descriptively. The results showed that the chemical quality of fresh milk on average had a protein content of 4.71%, fat of 6.70%, and specific gravity of 1.3139 g/ml. It was concluded that the chemical quality of fresh milk at Wayang Dairy Farm is very good and in accordance with the Indonesian national standard (SNI) 2011.